Innovation Ecosystem for Resource-Rich Countries: Validation of Entrepreneurship Framework for Qatar as a Case - Mohammad I. Al-Housani (19170967) (2024)
This study investigated how entrepreneurship can reshape resource-based countries such as Qatar into more diverse, sustainable, and knowledge-driven economies. By integrating both exploratory and quantitative research methods, it closely examines how various elements, including government policies, societal values, financial aids, and technological advancements, interact to influence entrepreneurial success. A significant part of the research involves a survey design based on initial qualitative research from a previous study to test the effectiveness of these strategic suggestions. This paper presents targeted recommendations for stakeholders to enhance entrepreneurship education, streamline business regulations, and introduce a national entrepreneurship zone (ENT-Q) facilitated by a digital platform (Ryadah). These steps aim to improve the entrepreneurial environment significantly, making it easier to access crucial business information, support small businesses through dedicated funds, and shift towards a diversified and knowledge-based economy. The anticipated result is better policymaking in entrepreneurship, increased entrepreneurial activity and success, and a move away from reliance on traditional oil and gas sectors. By offering a detailed plan for promoting entrepreneurship in resource-rich settings, this paper contributes valuable insights into economic diversification and sustainable development, providing actionable strategies that can be adapted to similar economies worldwide in a manner that is more accessible and understandable. Other Information Published in: Sustainability License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/su16072940